THE EFFECT OF COMPLEMENTARY FOOT SOAK THERAPY USING RED GINGER BOILED WATER TO LOWER BLOOD PRESSURE IN THE ELDERLY: CASE REPORT - Khusnil Fadhliat Salis; Agis Taufik; Asep Iskandar; Galih Noor Alivian (International Journal of Biomedical Nursing Review, 2024)
Introduction: Hypertension is a condition where humans experience an increase in blood pressure above normal, namely 140/90 mmHg. Based on data from the World Health Organization (WHO), it shows that around 1.28 billion adults suffer from hypertension aged 30-79 years worldwide. Hypertension in the elderly is caused by decreased elasticity of the oral walls, thickening of the heart valves which makes the valves stiff, decreased pumping ability of the heart, decreased elasticity of peripheral blood vessels, increased resistance of peripheral blood vessels, and decreased function of blood vessels. Purpose: Foot soak therapy using warm ginger water aims to improve blood circulation, reduce edema and improve muscle circulation. Methods: The research method used is the case study method. This intervention was given to 2 elderly people with hypertension, intervention was carried out 3 times a week with a duration of 15-20 minutes per meeting. Data analysis used in this research was by using the Wilcoxon test. Discussion: The client's blood pressure after being given the intervention decreased with an average blood pressure for the two elderly people of 143 mmHg (systolic) and 84 mmHg (diastolic). The Wilcoxon test results showed that the Sig (2-tailed) value for systolic and diastolic pressure was 0.027 (<0.05) Conclusion: There is a significant effect of providing foot soak therapy using boiled red ginger water on blood pressure in elderly people with hypertension.